2017
DOI: 10.2217/pgs-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring of Recommendations to Reduce Serious Cutaneous Adverse Drug Reactions: A Pharmacogenomics Approach

Abstract: The Health Sciences Authority launched a pharmacogenetics initiative in 2008 to facilitate evaluation of pharmacogenetics associations pertinent for Chinese, Malays and Indians in Singapore. The aim was to reduce the incidence and unpredictability of serious adverse drug reactions, with a focus on serious skin adverse drug reactions. This paper describes the gathering of evidence and weighing of factors that led to different genotyping recommendations for HLA-B*15:02 with carbamazepine and HLA-B*58:01 with all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…SCAR guides highlighted the importance of prompt withdrawal of drugs in suspected SCAR cases. Post-market reports of CBZ-induced SCAR cases subsequently decreased by >95% [26]. Usage of CBZ decreased modestly overall, though new CBZ users declined by 40%.…”
Section: Updates In Global Regulatory Science Pharmacovigilance Andmentioning
confidence: 97%
“…SCAR guides highlighted the importance of prompt withdrawal of drugs in suspected SCAR cases. Post-market reports of CBZ-induced SCAR cases subsequently decreased by >95% [26]. Usage of CBZ decreased modestly overall, though new CBZ users declined by 40%.…”
Section: Updates In Global Regulatory Science Pharmacovigilance Andmentioning
confidence: 97%
“…A comprehensive PGx panel (which need not be limited to one single technology) that includes all actionable PGx markers can also prevent cases of rare but serious and expensive ADRs such as SJS/TEN, which can cost from US $1740 to US$25,540 per episode [38]. Patients requiring carbamazepine can potentially derive more benefit for no [12]. The amount that patients are willing to pay may also be much more than US $114.…”
Section: Discussionmentioning
confidence: 99%
“…In Singapore, genotyping for HLA-B*15:02 allele is performed prior to initiation of carbamazepine therapy in patients of Asian ancestry as standard of care for the avoidance of Steven's Johnson Syndrome and Toxic Epidermal Necrolysis (SJS/TEN) [12]. A cost-effectiveness analysis supported the decision by the Ministry of Health to subsidize the cost of the genotyping test.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies showed the effectiveness of HLA‐B*15:02 screening prior to carbamazepine prescription to prevent SJS/TEN (Chen et al, ). Later on, the HLA‐B*15:02 testing has become a reimbursable pharmacogenetic test in Taiwan since 2011 and in Singapore since 2013 (Dong, Sung, & Finkelstein, ; Tan‐Koi et al, ).…”
Section: Pharmacogenomicsmentioning
confidence: 99%